Applying Building Word to Improve Students’ Vocabulary Mastery at X Grade of Madrasah Aliyah Amaliyah Guppi - Fatmawati, Fatmawati; Taufan , Muhammad Ybnu (Jurnal Ilmiah Multidisiplin Amsir, 2024)
This research aims at finding out whether the use of the building word method is effective in improving students' vocabulary mastery. This research is an experimental research which the experimental group was pre-tested and post tested. The population in this research is all X Grade students at MA Amaliyah Guppi Mamuju. The sample of the research is the grade X students of MA Amaliyah Guppi which was taken using Cluster sampling technique. The data was obtained through vocabulary test that consists of 50 questions. The result of the study shows that the use of the building word method is effective in improving students' vocabulary mastery at the class X students of MA. Amaliyah Guppi. The result of the study shows that there are significant differences in the students' vocabulary after treatments were given. The result of the value of Sig. (2- tailed) .000 is smaller than the probability significance value of 0.05 and the calculated t-test is greater than the t-table value where 5.267>2.093. Simply, the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. Therefore, it can be concluded that the students' vocabulary mastery increased effectively by using building word method.